Goals, attention, and (UN) consciousness.[article]. - Dijksterhuis, Ap
In this article literature form neuroscience, cognitive psychology, and social cognition is integrated to discuss the relation between goals, attention, and consciousness. Goals are the tools with which people engage in volitional behavior. Whereas goal pursuit was traditionally assumed to be strongly related to consciousness, recent research and theorizing suggest that goals guide behavior through attention, and this guidance can occur outside of the person;s awareness. The crucial explanatory role of goals and attention in behavior, as well as the relative unimportance of consciousness, is examined in the context of social cognition research on goal priming. Furthermore three research domains are discussed that are relevant for the understanding of the implementation of volitional behavior:implicit learning, evaluative conditioning, and unconscious thought. It is concluded that these processes are goal dependent and that they need attention, but they can generally proceed without awareness. Finally, when people are consciously aware of their behavior or their goals, the effect can be beneficial as well as detrimental.